Safe, Healthy, and Sustainable Diets : Role of Food Regulatory Bodies and Innovations from India - Kathuria, Ashi Kohli; Anand, Deepika (World Bank, Washington, DC, 2022)
The paper discusses in brief India’s food regulatory system in the context of modernized frameworks and examples of well-developed and mature regulatory systems from five selected developed countries (Australia, New Zealand, Canada, the United States, and the European Union). India’s food regulator, the Food Safety and Standards Authority of India (FSSAI), established in 2008, has developed a modernized regulatory system that aligns well with the most recent food safety regulatory systems model of the World Health Organization (WHO) (2018). As it continues to strengthen the regulatory system to enhance food safety, FSSAI is applying innovative approaches to address the country’s unique challenges of food safety, public health, and sustainable diets. The paper discusses two of FSSAI’s innovations: (i) approaches to enhance the safety of food businesses operating in India’s huge informal food sector; and (ii) proactive direct engagement with consumers at scale to promote safe, nutritious, healthy, and sustainable diets by influencing behavior change, thus contributing to improvements in public health, nutrition, and environmental sustainability. The paper also describes FSSAI’s regulatory leadership during the COVID-19 pandemic to promote food safety. The paper concludes that the approaches and innovations adopted by FSSAI appear promising and there are lessons that could be adopted and adapted by other low- and middle-income countries (LMICs). These approaches have not yet been evaluated but do merit a deeper study and discussion that may well lead to expanding the roles food regulatory bodies could play in promoting food safety, public health and nutrition, and sustainability. Whether food regulators are well-placed to take on wider roles may vary by country and the system of public administration, but it is not inappropriate per se for regulators to have that expanded role.